A Survey on Recovering High Resolution images by Using Various Image Restoration Techniques - Krishnammal, N; Muthulakshmi, G (International Journal of Computer Sciences and Engineering, 2025)
Now a day‘s Image Restoration plays an essential task, since it is one of the major components of image processing technique. Image Restoration is used to enrich the appearance of the Image. It is the process of recovering original image from degraded image, which also reduces and removes the degraded image was found using Point Spread Function (PSF).Degradation transpires in many forms namely Motion blur, Noise, Camera Misfocus. There are two types of Image restoration namely degradation model and restoration model. Degradation model includes different types of noise model and restoration model includes different types of Deconvolution algorithm. Deconvolution algorithm is divided into two parts namely Blind Image Deconvolution algorithm and Non-blind Image Deconvolution algorithm. Blind Image Deconvolution algorithm will not have knowledge about how image was degraded. Non-Blind Image Deconvolution algorithm will have knowledge about how image was degraded. In this paper, surveys on various image restoration techniques for recovering high resolution images are analysed.